Курган эпохи палеометалла на побережье Хаджибейского лимана - Петренко, В.Г. (Материалы по археологии Северного Причерноморья, 2010)
The present article introduces materials received during the excavation of the barrow by Holodnaya Balka village, near Odessa. The burial complexes of different herders (nomadic) cultures, which envelop the chronological period from the Eneolith to the Early Iron Age, have been studied. The central grave — complex of the earliest stage of Usatovo culture — is of especial interest. This late eneolithic kurgan represents a ceremonial structure of a monumental type, which was organized as a «sanctuary» and associated with human sacrifice at the central pit. The kurgan is a central-plan structure, constructed of stones and earth: a mound, a dome-shaped protective covering and a fence of irregular laying (the cromlech, or so-called crepida). The cromlech contains a special megalithic construction of the «closed entrance» type. Anthropological research has shown that the eneolithic man buried on this kurgan belongs to the Proto-Europeoid branch of the ancient European race.